Relationship Between the Brain Natriuretic Peptide (BNP) Level and Remission of Diabetic Nephropathy with Microalbuminuria: A 3-Year Follow-Up Study - Seki, N.; Matsumoto, T.; Fukazawa, M. (Hormone and Metabolic Research, 2015)
The aim of the study was to examine the relationship between the brain natriuretic peptide (BNP) level and progression or remission of diabetic nephropathy with microalbuminuria for 3 years. The subjects were 100 Japanese type 2 diabetes mellitus outpatients with microalbuminuria. Associations between metabolic parameters at baseline [HbA1c, systolic blood pressure (SBP), urine albumin-creatinine ratio (ACR), estimated glomerular filtration rate (eGFR), and BNP] and the progression or remission of diabetic nephropathy were examined for 3 years. A total of 83 patients were examined at the end of the 3-year period, including 17 with remission to normoalbuminuria, 47 with continuing microalbuminuria, and 19 with progression to macroalbuminuria. HbA1c, ACR, and BNP differed significantly among the 3 groups (p=0.024, p<0.001, p=0.002, respectively). Among baseline factors, HbA1c and BNP were significant predictors of the percentage increase in ACR for 3 years in multiple linear regression analysis (β=0.259, p=0.02; β=0.299, p=0.007, respectively). In multivariate logistic regression analysis, HbA1c and ACR were independently associated with progression of diabetic nephropathy (p=0.008, p=0.023, respectively), and ACR and BNP were independently associated with remission of diabetic nephropathy (p=0.029, p=0.012, respectively). ROC curve analysis gave a cutoff value for BNP of 14.9 pg/ml for prediction of remission of diabetic nephropathy (p=0.016). The BNP level has a relationship with diabetic nephropathy and a low BNP level predicts remission of diabetic nephropathy. Therefore, monitoring of BNP can play an important role in management of diabetic nephropathy.
Keywords: diabetic nephropathy; microalbuminuria; brain natriuretic peptide